1928. Comparisons of 30-Day Admission and 30-Day Total Healthcare Costs Between Patients Who Were Treated With Oritavancin (ORI) or Vancomycin (VAN) for a Skin Infection in the Outpatient Setting. (26th November 2018) - Lodise, Thomas; Packnett, Elizabeth; Armstrong, Shannon; Redell, Mark
Abstract: Background: Hospital admission is a key cost driver in ABSSSI patients. Data suggest many ABSSSI patients are unnecessarily hospitalized and can be effectively and safely managed as outpatient (OP) at substantially lower cost. ORI a single-dose treatment has the potential to shift care from the inpatient (IP) to the OP setting in selected patients. In phase III trials, a single dose of ORI had comparable efficacy and safety to twice daily VAN for 7–10 days in ABSSSI patients who were treated in OP. Real-world comparative data on outcomes in ABSSSI patients using ORI in OP are limited. This study sought to compare the 30 day hospital admission rates and mean (standard deviation (SD)) healthcare costs among ABSSSI patients who received ORI or VAN as an OP. Methods: Retrospective cohort analysis of ORI and VAN patients in the Truven Health MarketScan ® Databases in 2016. Inclusion criteria: age ≥18 years; OP claim for ORI or VAN (index day (d)); a diagnosis of skin infection ≤7 d prior and 3 d after the index day; no IP discharge in 3 d prior to index day; ≥180 d of continuous enrollment prior to index day; ≥60 d of continuous enrollment post index day. Outcomes: 30 d hospital admissions and 30 d total healthcare costs. Results: In 2016, 120 and 6, 695 patients who received ORI and VAN, respectively, met inclusion criteria. Groups were well balanced at baseline (table). ORI patients had a significantly lower 30 d admission rate vs. VAN patients (5.8% vs. 16.2%, respectively, P = 0.002). Mean (SD) cost 30 d post index were comparable between ORI and VAN patients (10, 096 (8, 865) vs. 12, 779 (28, 773), respectively, P = 0.3). Conclusion: Results suggest ORI provides a single-dose alternative to multi-dose VAN for treatment of ABSSSI in OP and may result in lower 30 d hospital admission rates. Disclosures: T. Lodise, Melinta Therapeutics, Inc.: Consultant, Consulting fee. E. Packnett, Melinta Therapeutics, Inc.: Research Contractor, Research grant. S. Armstrong, The Medicine's Company: Employee, Salary. M. Redell, Melinta Therapeutics, Inc.: Employee and Shareholder, Salary.